2003
DOI: 10.1037/0097-7403.29.1.3
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of response, direction and place learning in an open field and T maze.

Abstract: Rats were trained to locate food in a response, direction, or place problem on an open field located at 2 positions. In Experiment 1, both the response and direction groups solved the problem. The place group failed to solve the task in approximately 300 trials. Experiment 2 demonstrated that rats need distinguishable start points to solve a place problem when neither a response nor a direction solution is available. Findings from Experiment 3 suggest that a combination of path traveled and distinct cues help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
106
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(128 citation statements)
references
References 51 publications
22
106
0
Order By: Relevance
“…Further, the claim that animals shift from place navigation to another form of responding is clearly at odds with the results of other studies showing that rats learn turning responses and directional responses rather easily but learn to navigate to places with more difficulty (Blodgett et al, 1949;Skinner et al, 2003). Because navigation to places requires more training (Blodgett et al, 1949;Skinner et al, 2003;Stringer et al, 2005), perhaps providing more extensive training in the water task would shift the response bias of rats from directional to place navigation, a possibility that was not investigated by Hamilton et al (2007). To evaluate this possibility, rats were given extensive hidden-platform training (240 trials) and tested for directional responding versus navigation to the absolute platform location at 4 separate points during training.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…Further, the claim that animals shift from place navigation to another form of responding is clearly at odds with the results of other studies showing that rats learn turning responses and directional responses rather easily but learn to navigate to places with more difficulty (Blodgett et al, 1949;Skinner et al, 2003). Because navigation to places requires more training (Blodgett et al, 1949;Skinner et al, 2003;Stringer et al, 2005), perhaps providing more extensive training in the water task would shift the response bias of rats from directional to place navigation, a possibility that was not investigated by Hamilton et al (2007). To evaluate this possibility, rats were given extensive hidden-platform training (240 trials) and tested for directional responding versus navigation to the absolute platform location at 4 separate points during training.…”
Section: Methodsmentioning
confidence: 67%
“…Studies using dry land mazes (Blodgett et al, 1949;Skinner et al, 2003;Stringer et al, 2005) have demonstrated that rats can learn to place navigate when the apparatus is repositioned during training and the site of reinforcement in the room is held constant. These studies have also shown that rats generally learn directional responses more readily than place responding, thus, the results of Experiments 1-3 and the findings from dry maze studies are largely consistent despite the differential emphasis on training versus testing manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…Skinner et al (2003) attempted to replicate the findings of Blodgett et al (1949) using an open field and aT-maze. Rats were trained on a response, direction, or place problem to a criterion of eighteen correct trial out of twenty.…”
Section: Place Learning Redefinedmentioning
confidence: 99%
“…(1949), and suggested that place learning, in the absence of a response or direction strategy, was very difficult. Skinner et al (2003) went on to test an alternative explanation for the poor place learning. They suggested that rats failed to solve the place problem when the maze was shifted left or right (translated) between trials because the rats failed to notice the change in the maze position or start point.…”
Section: Place Learning Redefinedmentioning
confidence: 99%
See 1 more Smart Citation